Tie Strength Analysis: New Metrics and Open Problems - Brandão, Michele A.; Moro, Mirella M. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2017: Anais do VI Brazilian Workshop on Social Network Analysis and MiningDO - 10.5753/brasnam.2017.3258, 2017)
The study of social ties has lead to building rigorous models that reveal the evolution of social networks and their dynamism. In this context, a central aspect is the strength of ties, which allows the study of the roles of relationships. Here, besides analyzing the strength of co-authorship ties, we also present a set of metrics and algorithms to measure such strength.